2003
DOI: 10.1007/s00535-002-1104-5
|View full text |Cite
|
Sign up to set email alerts
|

Combined interferon α2b and cyclosporin A in the treatment of chronic hepatitis C: controlled trial

Abstract: In patients with chronic hepatitis C; combined interferon and cyclosporin A treatment was more effective than interferon monotherapy. The benefit was mostly achieved in patients with a high viral load and HCV genotype 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
104
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(107 citation statements)
references
References 20 publications
2
104
0
1
Order By: Relevance
“…The NS5B serine/glycine polymorphism at position 556 or NS5A polymorphisms that distinguish genotype 2/3 from genotype 1 could potentially be responsible for the differences in CsA susceptibility. 27,28 Nevertheless, the data presented here points to a polymorphic region of NS5A as having the largest effect on CsA susceptibility.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The NS5B serine/glycine polymorphism at position 556 or NS5A polymorphisms that distinguish genotype 2/3 from genotype 1 could potentially be responsible for the differences in CsA susceptibility. 27,28 Nevertheless, the data presented here points to a polymorphic region of NS5A as having the largest effect on CsA susceptibility.…”
Section: Discussionmentioning
confidence: 63%
“…25 Studies that have demonstrated a beneficial effect of CsA on HCV have only been able to do so in genotype 1, generally in conjunction with interferon. [26][27][28][29][30] We used a forward genetics approach to investigate the mechanism of CsA inhibition of the HCV replicon. CsA selected for mutations in NS5A and NS5B.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports on anti-HCV effects of immunosuppressive agents such as cyclosporine. 16,17 In addition, antiretroviral therapy used for HIV suppression may confer additional suppression of HCV, ultimately enabling HCV clearance. 18 The mechanism for spontaneous clearance of chronic HCV infection observed in our coinfected patients post-OLT, however, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Controlled trials showed that a combination of CsA with IFN␣ is more effective than IFN␣ alone, especially in patients with a high viral load (4,5). Moreover, recent in vitro studies provided evidence that CsA prevents both HCV RNA replication and HCV protein production in an IFN␣-independent manner (6 -10).…”
mentioning
confidence: 99%